2016
DOI: 10.1159/000443649
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Is Associated with a Lower Risk of Dementia after a Stroke or TIA. The Rotterdam Study

Abstract: Background: Higher education is associated with a lower risk of dementia, possibly because of a higher tolerance to subclinical neurodegenerative pathology. Whether higher education also protects against dementia after clinical stroke or transient ischemic attack (TIA) remains unknown. Methods: Within the population-based Rotterdam Study, 12,561 participants free of stroke, TIA and dementia were followed for occurrence of stroke, TIA and dementia. Across the levels of education, associations of incident stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
3
31
1
1
Order By: Relevance
“…1). We excluded the study by Reitz and colleagues using data from the Rotterdam Study [14] due to overlap with a more recent publication from the same cohort [15] which had longer follow-up and a larger sample size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). We excluded the study by Reitz and colleagues using data from the Rotterdam Study [14] due to overlap with a more recent publication from the same cohort [15] which had longer follow-up and a larger sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve prospective cohort studies [15,37,42,5563] investigated the association between incident stroke and incident all-cause dementia (around 1.3 million participants and 131,217 stroke events; Appendix B, Table B2). The majority of studies included older adults and the analytic sample size ranged from 339 [62] to 799,069 [60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,[18][19][20][21]23,25,32 Adding demographics factors showed that the risk of incident dementia elevated in relation to older age especially > 80 years (RR 4.66, 95%CI; 2.36 to 9.22) and age 70 to 79 years (RR 2.68, 95%CI; 1.52 to 4.74) versus age 60 to 69 years. 28 33 Previous mental decline was the correlation of dementia in logistic regression analysis (OR 1.20, 95%CI; 1.10 to 1.40). 31 Cognitive impairment before stroke risk of dementia after stroke showed that cognitive impairment before stroke was associated with potential covariates and diagnosis of poststroke dementia in the Helsinki Stroke Ageing Memory study cohort (OR 5.76, 95%CI; 2.84 to 11.70).…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to a higher cognitive reserve in those stroke survivors who have higher education levels and therefore, higher tolerance to neurodegenerative pathology and cognitive decline [25]. It is also possible that those with higher education had higher socioeconomic status and more access to resources and financial support than those with lower education [26].…”
Section: Discussionmentioning
confidence: 99%